Studi Komparatif Penerapan Restorative Justice Di Negara IndonesiaDan Amerika Serikat - Andika Ramadhani Wibowo Mukti; Rahtami Susanti (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2023)
The concept of restorative justice is increasingly developing and being adopted by several countries in the worldwith different names, the United States calls it victim offender mediation, while in Indonesia it is known as theconcept of restorative justice. This study aims to find out the differences between the legal systems of Indonesiaand the United States, as well as find out the similarities and differences of restorative justice in Indonesia and theUnited States. The research method used is normative juridical with a comparative approach. The results of thestudy show that the differences in the legal systems in Indonesia and the United States are influenced by the formof the state, Indonesia with the form of a republican unitary state that adheres to a civil law legal system, in whichwritten legal regulations are used as laws and legal basis that must be obeyed by all citizens within the territory ofthe unitary Indonesia. Whereas the United States as a federal country that adheres to the common law legalsystem, has several laws that serve as its basis, federal law as the highest state law that applies to all states, andstate law that only applies to each state. In the application of restorative justice, Indonesia and the United Stateshave similarities, namely, its application is limited to minor crimes and applies to both juvenile and adult justice,the application of restorative justice aims as an effort to reduce inmates to prevent overcapacity in detentioncenters. The difference in the application of restorative justice in Indonesia is that laws regarding restorativejustice apply to all communities and regions within the scope of the unitary state, whereas in the United Stateseach state has different laws regarding the application of restorative justice, there are at least forty-five out offifty states that have incorporated restorative justice into state laws.